Compost utilization in production of horticultural crops - Ozores-Hampton, Monica (Boca Raton, FL : CRC Press, 2021)
"Compost Utilization in Production of Horticultural Crops provides information for the compost industry to develop horticulture production efforts and techniques. This highly practical book contains information applicable to current production issues facing the fruit and nuts, vegetable, and ornamentals and turfgrass industry. Written by scientific experts, chapters evaluate the uses of compost for greater crop yields and decreased plant disease and pesticide application, irrigation water and fertilizer demand. Considering compost use increases carbon sequestration, the book provides guidelines on converting safe waste materials into composted soil amendments while minimizing negative impacts on the environment. Chapters cover the diversity and variability on compost uses of available feedstocks; composting methods, application rates, methods and timing; and considers the benefits of application alone or combined with other organic or inorganic nutrient sources"--
Past, Present and Future of Compost in Horticulture Crop Production / Monica Ozores-Hampton -- Impact of Compost on Soil Health / Monica Ozores-Hampton -- Fertility Program Using Compost in Fruit Crops, Vegetable, and Field Ornamental Production / Monica Ozores-Hampton -- Organic Compost in Crop Production / Monica Ozores-Hampton -- Compost Utilization in Fruit Production / Fernando Alferez -- Compost Utilization in Vegetable Production / Monica Ozores-Hampton -- Compost Utilization in Ornamental and Nursery Crop Production / Craig Coker -- Compost Utilization in Turfgrass and Lawn Management / David Hill -- Utilization of Compost and Food Safety / Monica Ozores-Hampton -- Using Compost on Nematodes Management in Horticulture Crops / Monica Ozores-Hampton -- Compost Tea Foliar Disease Suppression in Horticulture Crops / Craig S. Coker and Monica Ozores-Hampton -- Compost Utilization and The Economic Impact in Crop Production / Rod Tyler.
OCLC-licensed vendor bibliographic record.
Keywords: Compost; Compost plants; SCIENCE / Environmental Science; TECHNOLOGY / Agriculture / General; TECHNOLOGY / Food Science